Naṃ yo ʼA rhaṅʻ Jāgara Matherʻ cī raṅʻ reʺ sāʺ ʼapʻ so Dvattiṃsālokadīpanī - Jāgara, Naṃ yo ʼA rhaṅʻ (Krīʺ pvāʺ reʺ Cā puṃ nhipʻ Tuikʻ, 1952)
On the Buddhist concept of the thirty-two components of human hody.